SPK Pemilihan Pestisida Tanaman Bawang Merah Dengan Metode WASPAS - zunaidi, edi; Setyawan Wibisono (STEKOM PRESS, 2022)
Farmers often have difficulty in choosing the pesticides to use. Where pesticide products are very widely circulated in the market and offer various advantages of each product, but farmers often experience incompatibility with what has been offered by each product. The inappropriate use of pesticides on shallots used by farmers can affect the yield of shallots. The WASPAS assessment criteria in the selection of pesticides on shallots consisted of price criteria weighing 40%, size criteria weighing 10%, area criteria weighing 30% and expiration criteria weighing 20%. The results of the recommendation for the selection of pesticides on shallots were obtained from the highest Q_i value. Of all the pesticides on shallot plants above, the highest Q_i value is Agrithane with a Q_i value of 0.897. Agrithane has the highest value because it has the lowest price where the price criterion has the highest percentage weight.